2015
DOI: 10.1016/j.immuni.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Passenger Mutations Confound Interpretation of All Genetically Modified Congenic Mice

Abstract: SUMMARY Targeted mutagenesis in mice is a powerful tool for functional analysis of genes. However, genetic variation between embryonic stem cells (ESCs) used for targeting (previously almost exclusively 129-derived) and recipient strains (often C57BL/6J) typically results in congenic mice in which the targeted gene is flanked by ESC-derived passenger DNA potentially containing mutations. Comparative genomic analysis of 129 and C57BL/6J mouse strains revealed indels and single nucleotide polymorphisms resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
185
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(191 citation statements)
references
References 47 publications
(77 reference statements)
3
185
3
Order By: Relevance
“…S3B), suggesting that AIM2 KO did not affect inflammasome priming by ALVAC in mouse BMDCs. In addition, recent studies reported that targeted mutagenesis in mice is prone to introduce potential passenger mutations in genetically modified mice (33). To further confirm the above observations, we used AIM2−/− mice generated on the C57BL/6 genetic background (20).…”
Section: Resultsmentioning
confidence: 99%
“…S3B), suggesting that AIM2 KO did not affect inflammasome priming by ALVAC in mouse BMDCs. In addition, recent studies reported that targeted mutagenesis in mice is prone to introduce potential passenger mutations in genetically modified mice (33). To further confirm the above observations, we used AIM2−/− mice generated on the C57BL/6 genetic background (20).…”
Section: Resultsmentioning
confidence: 99%
“…For the accuracy of experiments, all of the control mice were littermates (18). The TLR4 lps-del mice (C57BL/10ScN background, The Jackson Laboratory Number: 003752), ages 6 to 8 weeks and carrying a spontaneous deletion of TLR4, and littermates were purchased from the experimental animal center of Nanjing University (Nanjing, China; refs.…”
Section: Animal Treatmentsmentioning
confidence: 99%
“…Findings that BAD-deficient mice are less sensitive in a model of systemic TNF-mediated hepatitis (Yan et al 2013) could not be confirmed in an independent study (Ottina et al 2015). Of note, responses to TNF or glucose are strongly influenced by the genetic background of the mouse model used and, when poorly controlled for, can contribute to sometimes inconsistent findings (Leiter 2002;Vanden Berghe et al 2015). Combined deletion of BAD plus BIM (Kelly et al 2010) or BMF (Baumgartner et al 2013), respectively, did not result in any particular developmental phenotypes and revealed only mildly increased cell death resistance upon cytokine withdrawal, B-cell-specific lymphadenopathy, and increased susceptibility to spontaneous as well as radiation-induced tumorigenesis.…”
mentioning
confidence: 99%